IMPLEMENTATION SYSTEM OF SIMPLEX METHOD FOR OPTIMIZATION PROFIT - Imam Purwanto; Makmun (International Journal Science and Technology, 2023)
Companies that carry out production activities necessarily want the company's goals to be achieved, one of which is optimal profit. Maximum profit in production can be realized by planning the optimal amount of production. The purpose of this study consists of four, namely making a profit formulation to maximize the amount of production, determining the optimal number of brown bread variants that will be produced at Win Bakery, determining the maximum profit in producing bread at Win Bakery, and predicting profits for return on investment. This research was conducted using a linear programming model. Decision variables determine the decisions that will make to achieve the optimal solution. The objective function is a function that describes the goals or objectives in linear programming problems. Relating to the optimal use of resources to obtain maximum profit or to use minimum costs. A constraint function is a form of formulation of the obstacles faced in achieving the goal. The results obtained from the research are the decision variables, with X1 being the number of square chocolate bread productions and X2 is the number of round chocolate bread productions. The objective function of the profit per unit is to maximize Z = 1000X1 + 800X2. The constraint function is the raw material used in making chocolate bread. Furthermore, the optimization of production with POM-QM resulted in the number of square chocolate bread production of as many as 13 pieces and round chocolate bread as many as 25 pieces so that the profit gained in one day was Rp. 32,500. The next calculation, the break-even point by entering fixed costs, variable costs, and profits obtained results in units of 55 units and the total profit earned is Rp. 1,777,00.